Digital marketing communication education for PKK community in Simpang Kanan Village, Tanggamus Regency - Fajar Sasora; Erwin Putubasai; Eka Ubaya Taruna Rauf; Sodirin Sodirin; Ade Sandra Dewi; Nelson Nelson (Universitas Muhammadiyah Magelang, 2024)
Digital marketing communication has become essential for home-based businesswomen, particularly those involved in PKK (Family Welfare Empowerment Program). In Simpang Kanan Village, there is a low level of knowledge among PKK members regarding technology, especially digital marketing. Almost all PKK members market their products directly, limiting their market reach. This community service aimed to educate the partners about digital marketing communication to increase product sales. The methods used were socialization, practice, and mentoring. The results show that 70% of PKK members have improved their understanding of digital marketing communication, enabling them to create persuasive messages and utilize social media for product marketing.